Impairment of Nrf2 signaling in the hippocampus of P301S tauopathy mice model aligns with the cognitive impairment and the associated neuroinflammation - Ahmed Sabry Mohamed; Mahmoud ElKaffas; Karim Metwally; Mahmoud Abdelfattah; Eslam Ashraf Elsery; Ahmed Elshazly; Hossam Eldin Gomaa; Aziza Alsayed; Sara El-Desouky; Randa El-Gamal; Sara Elfarrash (BMC, 2024)
Abstract Mice transgenic for human P301S tau protein exhibit many characteristics of the human tauopathies, including the formation of abundant hyperphoshorylated tau filaments, the associated neuroinflammation and disease phenotype. However, the exact underpinning mechanisms are still not fully addressed that hinder our understanding of the tauopathy diseases and the development of possible therapeutic targets.Methods: In the current study, hippocampus from three disease time points (2, 4 and 6 months) of P301S mice were further characterized in comparison to the age and sex matched control wild type mice (WT) that do not express the transgene. Different spectrum of hippocampal dependent cognitive tests, biochemical and pathological analysis were conducted to understand the disease progression and the associated changes in each stage. Results: Cognitive impairment was manifested as early as 2 months age, prior to the identification of tau aggregation and phosphorylation by immunostaining. P301S mice manifested an increased pro-inflammatory related changes at mRNA transcription level (IL-1b and IL17A) with the progression of the disease and when compared to the WT mice of the same age. Among the identified genes in the current study, the nuclear factor (erythroid-derived 2)-like 2 (Nrf2) genes expression that is considered as the master regulator of an endogenous inducible defense system was significantly impaired in P301S mice by 4 and 6 months when compared to healthy WT controls. A data that was also supported by the immunostaining of the serial brain sections including the both brain stem and hippocampus. The current result is suggesting that the downregulation of Nrf2 gene and the impaired Nrf2 dependent anti-inflammatory mechanisms in P301S mice brain is possibly contributing -among other factors- in the neuroinflammation and tauopathy, and that modulation of Nrf2 signaling impairments can be further investigated as a promising potential therapeutic target for tauopathy.